Emaranhamento, medidas quânticas gerais e instrumentos quânticos - Pinto, Douglas Franco (2023)
In this work, the asymmetry properties of quantum states associated with the Hamiltonian generator of the dynamics of the magnetic dipole interaction are investigated and their relationships with the production of entanglement are identified. Are also explored the types of separable or partially entangled quantum states that can be used as a resource in the entanglement distribution protocol, where we use IBM quantum processors to test the results with simulations and experiments performed remotely. Furthermore, a state preparation algorithm is presented that allows simulating and performing experiments with general quantum measurements and quantum instruments, as well as noisy quantum channels. In the topic about the properties of asymmetry and entanglement production, classes of pure and mixed quantum states consisting of 2 qubits evolved under magnetic dipole interaction (MDI) are considered.The asymmetry measure used is based on the Wigner-Yanase skew information between the quantum state and the Hamiltonian of the IDM, whose dependence is provided by the interaction parameters and initial conditions of the system. The local asymmetry associated with the evolved state is investigated, which is characterized by its dependence on the interaction parameters, local and temporal parameters, allowing the establishment of indirect relationships with the entanglement dynamics generated by MDI. The asymmetry related to the element of the unitary group responsible for the dynamics of the MDI is also analyzed, being useful to understand the dynamic character regarding the Wigner-Yanase asymmetry and to establish dynamic links with other properties. On the other hand, regarding the entanglement distribution protocol, the role of separable and partially entangled states are explored in the context of the Bell-diagonal class of states, analyzing the probabilistic entanglement distribution, where it involves selective projective measures, and the deterministic entanglement distribution, where it involves the action of non-selective general quantum measurements. Finally, with the proposal of a state preparation algorithm based on the relationship between the action of quantum channels and isometry, it was possible to carry out simulations and experiments on IBM quantum processors in general quantum measurements, quantum instruments and noisy quantum channels applied to qudits, allowing, in this way, to handle and develop in a simpler way the applications that until then were complex to simulate.